Kali Linux Penetration Testing Bible - Khawaja, Gus (John Wiley & Sons, Incorporated, 2021)
A comprehensive how-to pentest book, using the popular Kali Linux tools  Kali is a popular Linux distribution used by security professionals and is becoming an important tool for daily use and for certifications. Penetration testers need to master Kali's hundreds of tools for pentesting, digital forensics, and reverse engineering. Kali Linux Penetration Testing Bible is a hands-on guide for getting the most from Kali Linux for pentesting. This book is for working cybersecurity professionals in offensive, hands-on roles, including red teamers, white hat hackers, and ethical hackers. Defensive specialists will also find this book valuable, as they need to be familiar with the tools used by attackers.  This is the most comprehensive pentesting book on the market, covering every aspect of the art and science of penetration testing. It covers topics like building a modern Dockerized environment, the basics of bash language in Linux, finding vulnerabilities in different ways, identifying false positives, and practical penetration testing workflows. You'll also learn to automate penetration testing with Python and dive into advanced subjects like buffer overflow, privilege escalation, and beyond.  Gain a thorough understanding of the hundreds of penetration testing tools available in Kali Linux  Master the entire range of techniques for ethical hacking, so you can be more effective in your job and gain coveted certifications  Learn how penetration testing works in practice and fill the gaps in your knowledge to become a pentesting expert  Discover the tools and techniques that hackers use, so you can boost your network's defenses  For established penetration testers, this book fills all the practical gaps, so you have one complete resource that will help you as your career progresses. For newcomers to the field, Kali Linux Penetration Testing Bible is your best guide to how ethical hacking really works.